Aspekt misyjny teologicznego wymiaru ruchów migracyjnych - Balwierz, Marian (Śląskie Studia Historyczno-Teologiczne, 1981)
The Church in Europe realizes her duty of evangelization with help of immigrants, who perform this activity in different ways. The most important of them are the pastoral, oecumenical and missionary activities. Knowing this truth, the Church since the Fourth Lateran Council (1215) has taken care of immigrants in various ways. At present, people who look for work dominate in the group of European immigrants. It is obvious from ecclesiastical teaching about the value of human work, that the care of the whole human person is the first concern of Church’s approach to the phenomenon of immigration. The whole Church realizes this care in two more practical ways. The first of them is the defence of personal rights and human dignity of immigrants. The second duty is her pastoral care regarding religious life of those people. Both of them tend towards neutralization of the danger of desintegration in the immigrant’s life. The principle of priority of human spirit before material realm of man has dominated this very practical approach of the Church to the phenomenon of immigration. The same doctrinal principle is typical for the evangelizing activity of the Church among and by immigrants in the modern Europe. Paying attention to the various problems of immigrant’s life, the Church has first of all established some proper pastoral institutions for those people. Some of those institutions do not only take care of their souls, but also help them to solve all other particular problems of their life. A special attention is paid here to the children of immigrants. The welfare work of the Church is also very important here. The Church has started also to celebrate a „Day of Immigrant” every year, in order to increase her apostolic work in and by the immigrant's world. Those and other projects can bring immigrants as well as their families to Jesus Christ, and therefore they are ways of realization of Church's mission. A further verification of such a conclusion brings forward the papal theology of immigration. The phenomenon of immigration is seen by popes Pius XII, Paul VI and John Paul II as a reality strictly connected to the Mystery of Incarnation of God’s Son. It is also connected to the Mystery of God’s Revelation and the Mystery of Man taken in his religious experience. Four theological thoughts, namely: about God the Father of all the people, about the unifying task of the Holy Spirit, about the Church existing as an evangelized-evangelizing reality, and about the whole Church as being a missionary reality, have dominated this particular teaching of the Church. This reflection leads to the conclusion, according to which it is possible to say, that local Churches realize an integral part of their duty to build the universal Church and to evangelize the world by their proper work among immigrants.